2007
DOI: 10.1124/dmd.106.014126
|View full text |Cite
|
Sign up to set email alerts
|

NC100668, a New Tracer Tested for Imaging of Venous Thromboembolism: Pharmacokinetics and Metabolism in Humans

Abstract: ABSTRACT:The 99m Tc-complex of NC100668 [Acetyl-Asn-Gln-Glu-Gln-Val-SerPro-Tyr(3-iodo)-Thr-Leu-Leu-Lys-Gly-NC100194] is a new tracer tested for nuclear medical imaging of venous thromboembolism. NC100668 is a 13-amino acid peptide with a Tc-binding chelator

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In one recent publication it was reported that the Tat peptide enters the cytosol under conditions where all known forms of endocytosis have been knocked down (50). However, the concentration used in this study was rather high, approximately 10 µg/ml, when compared with the expected human dose of 50-100 µg for SPECT imaging with targeting peptides (51,52). Even if these positively charged peptides turn out to be useful for other purposes, it is very unlikely that they will be useful for medical imaging of cytosolic targets.…”
Section: Cellular Uptake Of Positively Charged Moleculesmentioning
confidence: 88%
“…In one recent publication it was reported that the Tat peptide enters the cytosol under conditions where all known forms of endocytosis have been knocked down (50). However, the concentration used in this study was rather high, approximately 10 µg/ml, when compared with the expected human dose of 50-100 µg for SPECT imaging with targeting peptides (51,52). Even if these positively charged peptides turn out to be useful for other purposes, it is very unlikely that they will be useful for medical imaging of cytosolic targets.…”
Section: Cellular Uptake Of Positively Charged Moleculesmentioning
confidence: 88%
“…Much higher amounts have to be injected to obtain concentrations above 10 µM for more than a few seconds in blood and reach such concentrations in the diseased tissues. Thus, the dose needed to obtain the membrane-penetrating properties for such peptides is rather high, especially when compared to the expected human dose of 50–100 µg for two targeting peptides for SPECT imaging, with which one of the authors has been working [37,38].…”
Section: Binding Of Cpps To Cells and Uptake Via Endocytosismentioning
confidence: 99%